Continuities in Emotion Lateralization in Human and Non-Human Primates - Lindell, Annukka K. (Frontiers in Human Neuroscience, 2013)
Where hemispheric lateralization was once considered an exclusively human trait, it is increasingly recognized that hemispheric asymmetries are evident throughout the animal kingdom. Emotion is a prime example of a lateralized function: given its vital role in promoting adaptive behavior and hence survival, a growing body of research in affective neuroscience is working to illuminate the cortical bases of emotion processing. Presuming that human and nonhuman primates evolved from a shared ancestor, one would anticipate evidence of organizational continuity in the neural substrate supporting emotion processing. This paper thus reviews research examining the patterns of lateralization for the expression and perception of facial emotion in nonhuman primates, aiming to determine whether the patterns of hemispheric asymmetry that characterise the human brain are similarly evident in other primate species. As such, this review seeks to enhance understanding of the evolution of hemispheric specialization for emotion, using emotion lateralization in nonhuman primates as a window through which to view emotion lateralization in humans.